How Do Corporate Tax Hikes Affect Investment Allocation within Multinationals? - Antonio De Vito; Martin Jacob; Dirk Schindler; Guosong Xu (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies how corporate tax hikes transmit across countries through multinationals' internal networks of subsidiaries. We build a parsimonious multicountry model to underscore two opposing spillover effects: While tax competition between countries generates positive investment spillover, intra-firm production linkages predict negative spillover. Using subsidiary-level data and exogenous corporate tax hikes, we find that local business units cut investment by 0.4% for a 1% increase in foreign corporate tax. This result highlights the importance of production linkages in propagating foreign tax shocks, as the supply-chain-induced negative spillover dominates the positive spillover effect suggested by the conventional wisdom of tax competition.
Keywords: 330; tax hike; investment; internal networks; multinationals; spillover effects